What to expect from iOS 5. - Bookwalter, J. R. (Mac life)
Just when you thought you knew iOS 4.3, rumors of a summer release for iOS 5 start building steam. Here's how we predict Apple's next mobile OS will change your iPhone, iPad, and iPod touch.